1996
DOI: 10.1200/jco.1996.14.5.1565
|View full text |Cite
|
Sign up to set email alerts
|

Intensive outpatient adjuvant therapy for breast cancer: results of dose escalation and quality of life.

Abstract: A dose of CY at 2,000 mg/m2 can be administered every 2 weeks with DOX and G-CSF for eight cycles in the outpatient setting with manageable toxicity. The majority of women described levels of physical symptoms and emotional distress as tolerable during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…In the study by Cinar et al (2009), the hemodialysis patients had a mean score of 68.94±14.77. In another study by Swain (1996), the patients with breast cancer had a mean score of 51.46±9.97 .The mean scores revealed by the present study are in parallel with those of similar studies, which might be attributed to the idea that human beings, who are bio-psycho-social creatures, produce similar reactions to illness across cultures.…”
Section: Discussionsupporting
confidence: 86%
“…In the study by Cinar et al (2009), the hemodialysis patients had a mean score of 68.94±14.77. In another study by Swain (1996), the patients with breast cancer had a mean score of 51.46±9.97 .The mean scores revealed by the present study are in parallel with those of similar studies, which might be attributed to the idea that human beings, who are bio-psycho-social creatures, produce similar reactions to illness across cultures.…”
Section: Discussionsupporting
confidence: 86%
“…However, it can be noted that the incidence of severe neutropenia, thrombopenia and febrile neutropenia did not increase from cycle 1 to cycle 4. In previously published studies of high-dose doxorubicin-cyclophosphamide regimen with rG-CSF but without stem cell transplantation (Shipp et al, 1995;Swain et al, 1996), thrombocytopenia is generally the dose-limiting toxicity, this appears to be cumulative and increases significantly between the first and last cycle (Shipp et al, 1995). These toxicities occur in the same range of doses as those used in our study: cyclophosphamide 2000 mg m -2 ; doxorubicin 40 mg m -2 every 2 weeks (Swain et al, 1996); cyclophosphamide 4000 mg m -2 ; doxorubicin 70 mg m -2 every 3 weeks for 4 cycles (Shipp et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The use of haematopoietic growth factors and/or peripheral stem cells allows regimen to be designed (Basser et al, 1995;Swain et al, 1996;Shipp et al, 1995;Stoppa et al, 1997;Viens et al, 1997) in which dose and dose intensity are significantly increased. These can then be given safely, as out patient first-line treatment with the objective of improving chemotherapy response and disease prognosis in the whole patient population.…”
mentioning
confidence: 99%
“…Data from Epping-Jordan et al (1999), for example, suggested that upward of 80% of patients report low distress as they cope with cancer treatments and recover. Thus, researchers might consider including, rather than excluding, those with premorbid conditions, particularly depressive or anxiety disorders, as well as including only those with moderate to high levels of distress.…”
Section: Patient Variablesmentioning
confidence: 99%